Cancellous and cortical bone mineral density around an elastic press-fit socket in total hip arthroplasty: A prospective 2-year follow-up study using quantitative CT BMD measurements in 25 patients. (1st November 2016) - Pakvis, Dean F M; Heesterbeek, Petra J C; Severens, Marianne; Spruit, Maarten
Abstract : Background and purpose — The acetabular component has remained the weakest link in hip arthroplasty for achievement of long-term survival. One of the possible explanatory factors for acetabular failure has been acetabular stress shielding. For this, we investigated the effects of a cementless elastic socket on acetabular bone mineral density (BMD). Patients and methods — During 2008–2009, we performed a single-center prospective cohort trial on 25 patients (mean age 64 (SD 4), 18 females) in whom we implanted a cementless elastic press-fit socket. Using quantitative BMD measurements on CT, we determined the change in BMD surrounding the acetabular component over a 2-year follow-up period. Results — We found a statistically significant decrease in cancellous BMD (−14% to −35%) and a stable level of cortical BMD (5% to −5%) surrounding the elastic press-fit cup during the follow-up period. The main decrease was seen during the first 6 months after implantation. During the second year, cancellous BMD showed a further decrease in the medial and lower acetabular regions. Interpretation — We found no evidence that an elastic press-fit socket would prevent acetabular stress shielding during a 2-year follow-up.